Pengaruh Pelatihan dalam Rangka Peningkatan Keterampilan dan Motivasi Kerja terhadap Kinerja Dosen pada Jurusan Administrasi Bisnis Negeri Pontianak - Abdullah, Abdullah; Fahrizal, Meizi; Herdiansyah, Dedi (Jurnal Aplikasi Manajemen, 2009)
Polytechnic in National Education is one of professional Education. Professional Education is more stressing the Ability and the implementation of knowledge basic of concepts and conduction in field detail. Learning process in polytechnic is directed to outcome the graduated owned the certainly competence, such as the ability supported with the ability to analize at certainly level. By this competence it's expected that polytechnic graduate are ready to work. To gain the outcome ready to work, training ang work motivation the polytechnic's lecturer is needed and planned well by the institution. From the result of this , the influence of training to the lectuirer of work performance has the positive fact. This means the training conducted by the institution has the fact to the students in learning process and by that it's expected the outcomes have the the quality and able to competence. Mean while the influence of motivation of lecture's work performance has a negative fact. It's due to the incentive, reward and the rate of lectures welfare is not optimal to treated by institution. For that the institution has to think the cases so that the motivation of lecture's work performance is no loyer decreasing. Mean while the influence of training and the motivation of lecture's work performance has a positive fact stimously.